Pengaruh komunikasi persuasif terhadap tingkat pengetahuan pada pasien tuberkulosis paru - Afrida Afrida; Lolita Sari; Dina Dwi Nuryani (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI), 2024)
Absract Background: Tuberculosis (pulmonary TB) is an infectious disease caused by Mycobacterium tuberculosis. Purpose: To determine the effect of the level of knowledge of pulmonary TB patients. Method: Quantitative research design using quasi experiment. The population is outpatients (pulmonary poly) who are still being treated at RSPBA, the sample size is 30 participants divided into 3 groups and each group contains 10 participants. The intervention of each group is different, namely by carrying out linear communication interventions, interactional communication interventions and transactional communication. Univariate data analysis obtained the average value of pre-test and post-test, bivariate analysis using t-test and multivariate. There is an influence on the level of knowledge that undergoes linear communication interventions, interactional communication interventions and transactional communication interventions. Results: Based on multivariate analysis with annova, it was found that there was no dominant communication on the knowledge level of pulmonary tuberculosis patients. There is an effect on the level of knowledge after the intervention of linear communication, interactional communication and transactional communication with a p-value <0.05. Based on the results of research on knowledge in the Transactional group, there was a significant influence between before the intervention and after the intervention, with a p value of 0.000 (p <0.05). Conclusion: Analysis used One way ANOVA. For health workers at Pertamina Bintang Amin Hospital, they can apply transactional communication in order to increase the knowledge of pulmonary TB patients in particular. Pendahuluan: Tuberkulosis (Tb Paru) merupakan salah satu penyakit infeksi yang disebabkan oleh Mycobacterium tuberculosis. Tujuan: Untuk mengetahui pengaruh tingkat pengetahuan pasien TB Paru. Metode: Desain penelitian kuantitatif menggunakan kuasi eksperimen. Populasinya adalah pasien rawat jalan (Poli paru) yang masih dalam pengobatan di RSPBA, jumlah sampelnya adalah 30 partisipan dikelompokkan menjadi 3 kelompok dan masing-masing kelompok berisi 10 peserta. Intervensi tiap kelompok berbeda-beda, yaitu dengan melakukan intervensi komunikasi linier, intervensi komunikasi interaksional dan komunikasi transaksional. Analisis data univariat didapatkan nilai rata-rata pre test dan post test, analisis bivariat menggunakan uji t dan multivariat. Terdapat pengaruh tingkat pengetahuan yang menjalani intervensi komunikasi linier, intervensi komunikasi interaksional dan intervensi komunikasi transaksional. Hasil: Berdasarkan analisis multivariat dengan annova, ditemukan bahwa tidak ada komunikasi yang dominan terhadap tingkat pengetahuan pasien tb paru. Terdapat pengaruh tingkat pengetahuan setelah dilakukan intervensi komunikasi linier, komunikasi interaksional dan komunikasi transaksional dengan p-value <0.05. Berdasarkan hasil penelitian tentang pengetahuan pada kelompok transaksional terjadi pengaruh yang signifikan antara sebelum dilakukan intervensi dan sesudah dilakukan intervensi, dengan p value 0.000 (p<0.05). Simpulan: Analisis menggunakan One way ANOVA. Bagi tenaga kesehatan di RS Pertamina Bintang Amin bisa menerapkan komunikasi transaksional dalam rangka meningkatkan pengetahuan pasien tb paru khususnya.